ANALISIS OPTIMISASI PROGRAM KUADRATIK DENGAN FUNGSI PENALTY - Roberto Parujian Sitanggang; Lasker Pangarapan Sinaga (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2023)
This study aims to analyze the optimality of a quadratic program model using the penalty function. The analysis is carried out in each case that has been made so that in each case optimal results are obtained. There are many methods that can be used to solve the quadratic program problem but in terms of the number of iterations, this research uses the penalty function and then implements it into the Matlab programming language. The results obtained in this study indicate that by using the penalty function as a parameter, the optimal value of a function can be obtained. The results of the analysis will also be more optimal by using the lagrange method depending on the parameter values obtained.